Rod Serling's Vast Promised Land: Battling Sponsors, Debating the FCC and Fighting for Mature Television, 1959-1966. - Yogerst, Chris (Historical Journal of Film, Radio & Television, 2018)
This article explores the 'public' television career of Rod Serling, drawing upon the collection of his papers held by the Winsonsin Historical Society, University of Wisconsin, Madison. Serling is best known as creator of the science fiction television anthology series The Twilight Zone (1959-1964) but his place in American television history is not defined solely by that one series. The article demonstrates how Serling responded to the changing institutional and cultural contexts of television broadcasting. It focuses in particular on his appearances before the Federal Communications Commission and his advocacy of creative freedom against censorial and sponsors' intervention. It concludes with an assessment of Serling's place in television history and his role as a 'godfather' of American Quality Television.